PENGEMBANGAN E-MODUL BERBASIS MEDIA SOSIAL INSTAGRAM PADA PEMBELAJARAN GRAMATIK BAHASA JERMAN SEBAGAI SUMBER BELAJAR MANDIRI - Nurfadzilah, Vina; Sudarmaji, Sudarmaji (UNIB Press, 2022)
The goals of this research were to 1) develop an Instagram-based e-module in German grammatical learning as a self-directed learning resource and 2) determine the feasibility of the Instagram-based e-module in German grammatical learning as a self-directed learning resource. This is a research and development using 4-D model (Define, Design, Develop, Disseminate). There were front-end analysis, student analysis, task analysis, concept analysis, and specification instructional objectives at the define stage. At the design stage, the initial design of e-module was made. At the develop stage, the expert validators provide assessments of the e-module followed by product testing and providing responses by German teacher and learners. In the last stage, the Instagram-based e- module in German grammatical learning as a self-directed learning resource was disseminated. The assesments obtained were 83% in the